Revitalisasi Tradisi Dekah Desa sebagai Media Syiar Islam dan Pelestarian Budaya Lokal di Era Digital - Haikal Al Fiqri; Ahmad Naufal Mumtaz; Ulfa Dwi Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2026)
This study examines the preservation and revitalization of the dekah desa tradition in Dusun Pabregan, Andong District, Boyolali Regency, as a manifestation of cultural values and Islamic da'wah. Previous studies on local traditions have predominantly focused on cultural preservation and religious values separately, while limited attention has been given to understanding how local traditions function simultaneously as a medium of Islamic da'wah and adapt to contemporary social developments. Therefore, this study aims to explore the relationship between local cultural practices and Islamic teachings within the dekah desa tradition, particularly in the context of maintaining its relevance in the modern era.This research employs a qualitative approach through field research methods by collecting data directly from the research site. The study adopts the perspective of living Qur'an and utilizes George H. Mead's symbolic interactionism theory to analyze the social processes underlying the formation and continuity of the tradition. The findings indicate that dekah desa represents a synthesis between local culture and Islamic values, reflected in ritual practices such as the gunungan procession, goat slaughtering, slametan, and art performances integrated with Islamic messages. Beyond functioning as an expression of gratitude for agricultural blessings, the tradition also serves as a contextual medium of da'wah through religious activities and culturally based performances. Furthermore, the study finds that the continuity of this tradition requires active participation from the community, particularly the millennial generation, through digital innovation and social media utilization to strengthen cultural awareness and ensure the sustainability of dekah desa in the contemporary era. Thus, dekah desa continues to exist as a representation of harmony between local cultural identity and Islamic teachings.